2015
DOI: 10.3844/ajebasp.2015.160.165
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Employees’ Turnover Intentions: Evidence from Private Educational Institutions

Abstract: In today's competitive environment, the development and retention of human capital has become a serious concern for organizations. This study aims to study the antecedents of employees' turnover intentions in private educational institutions. A closed ended questionnaire was distributed among 200 employees of different educational institutions. One hundred and seventy eight of them responded with total response rate of 79%. Regression analyses were performed to test the hypotheses set forth. The findings of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
0
9
0
10
Order By: Relevance
“…A strong emotional attachment between the employee and the organization will reduce the employee's turnover intention. The results of previous studies found the organizational commitment had negative effects to the turnover intention (Fitriany et al, 2011;Joo & Ready, 2012;Long et al, 2012;Mehrad & Fallahi, 2014;Bateh & Heyliger, 2014;Siddiqui & Jamil, 2015;Srimindarti et al, 2015;Sun et al, 2016). But Yasmin and Marzuki (2015) found that organizational commitment had no effect on turnover intention.…”
Section: Introductionmentioning
confidence: 40%
See 3 more Smart Citations
“…A strong emotional attachment between the employee and the organization will reduce the employee's turnover intention. The results of previous studies found the organizational commitment had negative effects to the turnover intention (Fitriany et al, 2011;Joo & Ready, 2012;Long et al, 2012;Mehrad & Fallahi, 2014;Bateh & Heyliger, 2014;Siddiqui & Jamil, 2015;Srimindarti et al, 2015;Sun et al, 2016). But Yasmin and Marzuki (2015) found that organizational commitment had no effect on turnover intention.…”
Section: Introductionmentioning
confidence: 40%
“…This finding shows that if employees felt comfortable with his supervisor's leadership style applied will influence in the increase of job satisfaction (Fitriany et al, 2011;Joo & Ready, 2012;Mehrad & Fallahi, 2014;Long et al, 2014;Bateh & Heyliger, 2014;Siddiqui & Jamil, 2015;Sun et al, 2016).…”
Section: Regression Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…Hasil penelitian yangmenguji hubungan stres kerja dengan intensi keluar oleh Rai (2015) menyatakan bahwa stres kerja secara signifikan mempengaruhi intensi keluar, dimana ketika karyawan memiliki tingkat stress kerja yang semakin tinggi maka intensi keluar pada perusahaan juga akan semakin meningkat. Penelitian Siddiqui and Jamil (2015), Ketabchi and Hazraty (2015) Berdasarkan hasil analisis jalur substruktural 2 yang disajikan pada Tabel 4, maka persamaan strukturalnya adalah: Nilai determinasi total sebesar 0,662 mempunyai arti bahwa sebesar 66,2% variasi turnover intention dipengaruhi oleh variasi stres kerja dan komitmen organisasional, sedangkan sisanya sebesar 33,8% dipengaruhi oleh faktor lain yang tidak dimasukkan ke dalam model penelitian.…”
Section: Pendahuluanunclassified